Book Reviews - Christien Klaufus, Book Review Editor (European Review of Latin American and Caribbean Studies, 2016)
The Improbable Conquest: Sixteenth Century Letters from the Rio de la Plata, por Pablo García Loaeza y Victoria L. Garrett, 2015; reseñado por Judith Farberman Urban Space as Heritage in Late Colonial Cuba: Classicism and Dissonance on the Plaza de Armas of Havana: 1754-1828, by Paul Niell, 2015; reviewed by Joseph L. Scarpaci El Jefe Político. Un dominio negociando en el mundo rural del Estado de México. 1856-1911, por Romana Falcón, 2015; reseñado por Raymond Buve Miedo negro, poder blanco en la Cuba colonial, por Jorge Camacho, 2015; reseñado por Oleski Miranda Navarro Revolutionary Parks: Conservation, Social Justice, and Mexico’s National Parks, 1910-1940, by Emily Wakild, 2011; reviewed by Grant Burrier Sandino’s Nation: Ernesto Cardenal and Sergio Ramírez Writing Nicaragua, 1940-2012, by Stephen Henighan, 2014; reviewed by Grace A. Gomashie La cancha peronista. Fútbol y política (1946-1955), edited by Raanan Rein, 2015; reviewed by Alexis Sossa Rojas Chile y la Guerra Fría global, edited by Tanya Harmer and Alfredo Riquelme Segovia, 2014; reviewed by Ángela Vergara Challenging Social Inequality: The Landless Rural Workers Movement and Agrarian Reform in Brazil, edited by M. Carter, 2015; reviewed by Rebecca Tarlau Brazil: Reversal of Fortune, by Alfred P. Montero, 2014; reviewed by Edgar J. Marcolin Latin American Documentary Filmmaking – Major works, by David William Foster, 2013; reviewed by Leontien Cremers Telling and Being told: Storytelling and Cultural Control in Contemporary Yucatec Maya Literatures, por Paul Worley, 2013; reseñado por Ana Ugarte Bachata and Dominican Identity/La bachata y la identidad dominicana, by Julie Sellers, 2014; reviewed by Grant D. Moss Entrepreneurial Selves: Neoliberal Respectability and the Making of a Caribbean Middle Class, by Carla Freeman, 2014; reviewed by Emiel Martens